How crime severity predicts victim willingness to meet the offender - Batchelor, D (American Psychological Association, 2022)
Policy and practice are often based on the assumption that victims of serious crimes are less willing to take part in restorative justice schemes than victims of minor crimes, despite a mix of contradictory existing evidence. The current studies use data from the Crime Survey for England and Wales (CSEW) to investigate predictors of victim willingness to meet the offender, using logistic regression models and path analysis. Study 1a was exploratory (CSEW years 2015-17), study 1b was a preregistered replication of study 1a (CSEW years 2017-2020). No support was identified for a negative or curved relationship between overall severity of the crime and willingness to meet the offender. Other dimensions of severity had varied independent effects; victims were more willing to meet when the crime had more impact on them, but less willing to meet when the offense had been violent. The relationship between violence and willingness to meet was partially mediated by the response of the criminal justice system, that is, police were more likely to have taken action when the crime was violent, and victims were less willing to meet the offender when the police had taken action. Overall, the findings suggest that victims of serious offenses should not be excluded from offers of meeting with the offender. The counterintuitive nature of the identified relationships indicate that exclusion criteria should be based on robust evidence not on intuition, and third parties should not make decisions on behalf of victims.